Evaluation of the proliferation markers Ki-67/MIB-1, mitosin, survivin, pHH3, and DNA topoisomerase IIα in human anaplastic astrocytomas - an immunohistochemical study - Gulati Sasha; Habberstad Andreas H; Torp Sverre H (BMC, 2011)
Abstract Background Histological malignancy grading of astrocytomas can be challenging despite criteria given by the World Health Organisation (WHO). Grading is fundamental for optimal prognostication and treatment, and additional biomarkers are needed to support the histopathological diagnosis. Estimation of proliferative activity has gained much enthusiasm, and the present study was designed to evaluate and compare novel immunohistochemical proliferative markers in human anaplastic astrocytomas. Methods Proliferative activity was determined in twenty-seven cases with antibodies reactive against the Ki-67 antigen, mitosin, survivin, pHH3, and DNA topoisomerase IIα, and they were mutually compared as well as related to mitotic activity. Results The markers correlated well with each other, but poorly with mitoses, probably because of small and squeezed tumour samples, in which identification of mitoses can be difficult. Positive association to overall survival was observed as well. Conclusions Our data show that these markers may assist significantly in the evaluation of proliferative activity in anaplastic astrocytomas and even have prognostic value.